2018
DOI: 10.1037/apl0000290
|View full text |Cite
|
Sign up to set email alerts
|

Are creative individuals bad apples? A dual pathway model of unethical behavior.

Abstract: Research has been inconsistent in its quest to discover whether dispositional creativity is associated with more or less unethical behavior. Drawing on social cognitive theory, we propose that moral disengagement and moral imagination are 2 parallel mechanisms that encourage or inhibit unethical behavior, and that which of these mediation processes occur depends on moral identity. Study 1, a 3-wave study of a food service organization, shows that employees high on both dispositional creativity and moral identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(63 citation statements)
references
References 85 publications
4
59
0
Order By: Relevance
“…By contrast, job seekers with low moral identities may respond more to salaries, benefits, and development prospects in the process of seeking jobs, instead of focusing on social and environmental responsibility. Based on the above analysis, this paper proposes the following hypothesis: At present, many studies continue with Study 2 after conducting Study 1 to verify a hypothesis convincingly (e.g., Duan, Xia, & van Swol, 2018;Keem, Shalley, Kim, & Jeong, 2018;Wang, Owens, Li, & Shi, 2018). Therefore, we will report on two studies that provide supporting evidence for the impact of environmental innovation on a firm's attractiveness, as well as the mediating effect of pride and the moderating effect of moral identity.…”
Section: The Moderating Role Of Moral Identitymentioning
confidence: 93%
“…By contrast, job seekers with low moral identities may respond more to salaries, benefits, and development prospects in the process of seeking jobs, instead of focusing on social and environmental responsibility. Based on the above analysis, this paper proposes the following hypothesis: At present, many studies continue with Study 2 after conducting Study 1 to verify a hypothesis convincingly (e.g., Duan, Xia, & van Swol, 2018;Keem, Shalley, Kim, & Jeong, 2018;Wang, Owens, Li, & Shi, 2018). Therefore, we will report on two studies that provide supporting evidence for the impact of environmental innovation on a firm's attractiveness, as well as the mediating effect of pride and the moderating effect of moral identity.…”
Section: The Moderating Role Of Moral Identitymentioning
confidence: 93%
“…Third, moral disengagement can emerge by obscuring or distorting the roles of harmful behaviors, such as ignoring and distorting harmful consequences, displacing and diffusing responsibility. Even though these cognitive mechanisms are discussed separately, previous researches operationalized moral disengagement as a single overarching construct (Chen et al, 2016;Connelly et al, 2016;Keem et al, 2018;Moore et al, 2012).…”
Section: Perceived Overqualification and Cyberloafingmentioning
confidence: 99%
“…As prior research has shown that demographic characteristics may influence the extent to which individuals engage in unethical behavior (Kish-Gephart et al, 2010; Keem et al, 2018) and that job tenure may affect the work behavior (Wright & Bonett, 2002), we controlled for the effects of demographic characteristics. Besides the demographics, we included age (in years), gender (1 = male, 2 = female), organizational tenure (in years), and education (1 = high school, 2 = college, 3 = university, 4 = master, 5 = PhD).…”
Section: Methodsmentioning
confidence: 99%